2018
DOI: 10.2337/dc17-1825
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasms Reported With Liraglutide or Placebo in People With Type 2 Diabetes: Results From the LEADER Randomized Trial

Abstract: LEADER was not primarily designed to assess neoplasm risk. Firm conclusions cannot be made regarding numeric imbalances observed for individual neoplasm types (e.g., pancreatic cancer) that occurred infrequently. LEADER data do, however, exclude a major increase in the risk of total malignant neoplasms with liraglutide versus placebo. Additional studies are needed to assess longer-term exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 36 publications
(33 reference statements)
1
45
0
4
Order By: Relevance
“…Regarding acute pancreatitis, pancreatic cancer and any malignant neoplasm as the main outcomes, the numbers of cases reported and the patient-years of observation in each arm were extracted from the main manuscripts reporting cardiovascular outcomes (including online supplementary material) or from specific reports about pancreatitis and/or neoplasms. [18][19][20][21][22] Table S2 (see Supporting Information) presents data on the adjudication process for acute pancreatitis. If the patient-years of observation were not explicitly stated in the manuscripts, the number of patients that could be observed for the main endpoint (major adverse cardiovascular events) was calculated from the mean (or median) duration of the trial times, approximated by subtracting the number of patients that did not provide data for this endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding acute pancreatitis, pancreatic cancer and any malignant neoplasm as the main outcomes, the numbers of cases reported and the patient-years of observation in each arm were extracted from the main manuscripts reporting cardiovascular outcomes (including online supplementary material) or from specific reports about pancreatitis and/or neoplasms. [18][19][20][21][22] Table S2 (see Supporting Information) presents data on the adjudication process for acute pancreatitis. If the patient-years of observation were not explicitly stated in the manuscripts, the number of patients that could be observed for the main endpoint (major adverse cardiovascular events) was calculated from the mean (or median) duration of the trial times, approximated by subtracting the number of patients that did not provide data for this endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…Among the numerous cancers associated with DM and metabolic syndromes 25 , the association between prostate cancer and DM is controversial, and some data suggest that patients with type 2 diabetes mellitus have a lower risk of prostate cancer compared with non-diabetic individuals 26 . However, a higher incidence of prostate cancer has been observed in large-scale studies carried out in Western countries 12 , as well as in Japan 9 . Furthermore, a higher body mass index and higher plasma C-peptide concentration increase prostate cancer mortality 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Further reductions in tumor growth and prostate cancer cell proliferation were observed by combination treatment with Ex-4 and metformin 11 , without a relationship to glucose reduction. Following our experimental demonstrations, the Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results trial (LEADER), showed that the GLP-1R agonist significantly decreased the prevalence of prostate cancer in patients with type 2 diabetes mellitus, suggesting that GLP-1R agonists attenuate prostate cancer growth in not only experimental animal models, but also patients with type 2 diabetes mellitus 12 . In our previous report, the anti-prostate cancer effect induced by Ex-4 was dependent on GLP-1R expression in cancer cells, and Ex-4 did not attenuate the proliferation of the human prostate cancer cell line ALVA-41 that does not express endogenous GLP-1R 10 .…”
Section: Introductionmentioning
confidence: 94%
“…The SAVOR‐TIMI 53 trial (Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus ‐ Thrombolysis in Myocardial Infarction) followed 16 492 individuals for a median of 2.1 years and reported fewer lung cancer events with saxagliptin vs placebo (54/326 vs 59/362; HR 0.91, 95% CI 0.63–1.32) [12]. Similarly, fewer lung cancer events were reported with liraglutide vs placebo (28/470 vs 33/419; HR 0.85, 95% CI 0.51–1.40) in the LEADER trial (Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results), which followed 9340 individuals for a median of 3.8 years [13]. Overall, these trials reported nonsignificant effect estimates, although it was neither powered nor designed to evaluate cancer as a study outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta‐analysis of 19 randomized controlled trials (RCTs), there was no association between incretin‐based drugs and lung cancer (relative risk 1.00, 95% CI 0.76–1.33) [9]. In subsequent RCTs, small imbalances were observed, with more lung cancer events with semaglutide than with placebo (8/155 vs 6/139) [11], while there were fewer lung cancer events with liraglutide (28/470 vs 33/419) and saxagliptin (54/326 vs 59/362) than with placebo [12,13]. None of these trials, however, was powered or designed to evaluate lung cancer as a safety outcome.…”
Section: Introductionmentioning
confidence: 99%